(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The effects of lubricant temperature on the dynamic behaviour of Nano-lubricated finite length journal bearings has been investigated in the present work. Modified time dependent Reynolds equation include the effect of oil film temperature was perturbed in order to calculate the eight dynamic coefficients (four stiffness, and four damping) required to evaluate the dynamic characteristics of the journal bearing, the oil film temperature was obtained by solving numerically the energy and heat conduction equations simultaneously with the Reynolds equation using appropriate boundary conditions. Suitable viscosity temperature model has been used to consider the effect of oil film temperature. The bearing lubricated with oil containing Titanium dioxide (TiO2 ) nanoparticles dispersed in to the base oil with various particle concentration. The effect of adding TiO2 Nano-particles with various particle concentrations (0.1%, 0.5%, 1%, 1.5% and 2%) in order to enhance its viscosity has been discussed. A validation to the mathematical model and the computer program written in Fortran90 prepared to solving the governing equation has been carried out by comparing the result for the dynamic coefficients (stiffness and damping) obtained in the present work with that obtained by Sheeja and Prabhu . The results seen to be in a good agreement with percentage of error less than 2%. The results obtained in the present study show that the bearing stiffness coefficients increases by 30% while the damping coefficients increased by 27% when the bearing lubricated with Nano lubricant that contains TiO2 Nano particles with particle concentration of (1.5%).